Audit committee effectiveness and timeliness of reporting: Indonesian evidence - Ika, Siti Rochmah; Mohd Ghazali, Nazli Anum (Emerald, 2012)
Purpose – The purpose of this paper is to examine the association between audit committee effectiveness and timeliness of reporting. Specifically, the paper investigates whether there is any relationship between effectiveness of an audit committee and submission of audited financial statements to the Indonesian Stock Exchange (IDX).